The Influence of the European Union on the Convergence of the Romanо-Germanic and Anglo-Saxon Law - David Tonievich Karamanukyan (Сибирское юридическое обозрение, 2012)
In this article a detailed analysis is given of the European Union's influence on the convergence of the Romanо-Germanic and Anglo-Saxon law.